THE LEGACY OF JADIDISM IN THE SYSTEM OF STATE-BUILDING AND SOCIO-CULTURAL MODERNISATION IN CONTEMPORARY UZBEKISTAN - SHARIPOVA , GUZAL; RUZIEVA , MUNISAKHON (WORLD INTERNATIONAL CONFERENCE ON SCIENCE, TECHNOLOGY AND EDUCATION, 2026)
This article analyses the theoretical and practical influence of the Jadid movement of the late 19th and early 20th centuries on contemporary development processes in the Republic of Uzbekistan. The paper examines the transformation of the ideas of the enlightenment reformers into fundamental elements of the state ideology of ‘New Uzbekistan’ and the concept of the «Third Renaissance». Based on an analysis of a wide range of sources, it is shown that the intellectual legacy of Mahmudkhodja Bekhbudiy, Abdurauf Fitrat, Abdulla Avloni and other leaders of the movement is viewed today not only as an object of historical memory, but also as an active instrument for legitimising contemporary reforms in the spheres of education, law and culture. Particular attention is paid to state memory policy, the institutionalisation of Jadidology, and the integration of the principles of ‘usul-jadid’ into the contemporary educational paradigm. The article substantiates the thesis that Jadidism acts as a unique non-Western model of modernisation, enabling the synthesis of national spiritual values with the achievements of global science and technology. It concludes that the ideas of the Jadids serve as an ideological bridge connecting the region’s historical past with the goals of sovereign development in the 21st century.